Economic outcomes of centralized procurements of gene therapy for patients with orphan diseases: inherited retinal dystrophy - N. А. Avxentyev; Yu. V. Makarova; V. V. Kadyshev (Фармакоэкономика)
Background. New pathogenetic treatment options, such as gene therapy, are now used to treat previously uncurable diseases. However, price of such treatment is high, especially in the case of orphan diseases, where costs may many-fold exceed the prices for other types of medication. This raises a question of optimal way of financing gene therapy in Russia.Objective: to evaluate economic consequences of centralizing procurement of gene therapy in 2021–2030 in the case of the drug indicated for treatment of biallelic RPE65 mutation-associated retinal dystrophy.Material and methods. Voretigene neparvovec is a new gene therapy that is used to treat RPE65 mutation-associated Leber congenital amaurosis and isolated retinitis pigmentosa. We estimated the number of patients (children and adults) that could be treated with voretigene neparvovec in 2021–2030 in Russia using demographic forecasting method, literature and expert data. Budget costs of treatment were estimated for two scenarios: status-quo, where gene therapy is purchased by regions for higher price, and centralized scenario with federal procurements and lower price for the drug.Results. Up to 100 children and 56 adults could be treated with voretigene neparvovec in 2021–2030 in Russia. Centralizing procurements at the expense of federal budget may save up to 20.7% or 1.8 billion rub. (1.13 billion rub. for children and 0.67 billion rub. for adults), compared to regional procurements.Conclusion. Centralizing procurements of expensive drugs intended for gene therapy of orphan diseases may save budget costs of the Russian Federation, compared to status-quo decentralized purchases.